Processo de gestão em incineração de resíduos sólidos de serviços de saúde: uma aplicação em materiais e aproveitamento energético - Reis, Renato Vaz dos (2004)
This dissertation covers aspects related to the incineration of the sanitary solid waste, using the thermic energy and ashes for other applications having in mind the consequences to the environment. In fact one of the major concern related to the environment is the continuous and cumulative generation of solid waste by the humanity. Therefore, we will cover one solution which consists on the usage of pyrolisis processes, incinerating this solid waste in specific high technology owens using air washers. The thermic energy deriveted from this process is reutilized for the in-house water heating for air conditioning or usage in boilers. The usage of the ashes is directed to usage in building materials (bricks, aggregators, etc...) reducing considerable the volume shipped for embankment. This project showed up as a very important issue because it resulted in no damage to the environment and reduced costs due to the energy sawings and utilization of subproducts from the process